2015
DOI: 10.1111/ahg.12105
|View full text |Cite
|
Sign up to set email alerts
|

Association of Monocyte Chemoattractant Protein‐1 (MCP‐1)‐2518A>G Polymorphism with Susceptibility to Coronary Artery Disease: A Meta‐Analysis

Abstract: SummaryWe attempted to systematically elucidate the association between monocyte chemoattractant protein-1 (MCP-1) -2518A>G polymorphism and risk of coronary artery disease (CAD). Eligible studies were identified through PubMed, EBSCO, and Web of Science Databases. The magnitude of MCP-1 polymorphism effect and its possible mode of action on CAD were estimated. The odds ratio (OR) with 95% confidence intervals (CI) were pooled in a specific genetic model to assess the association. A total of 21 studies were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The frequency of 17q25.3-rs6465657C allele was calculated in the control group of each study. 25 The prevalence rates of the C allele obtained from the individual studies were pooled together in the overall population or in various ethnic populations using the random-effects model when heterogeneity existed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of 17q25.3-rs6465657C allele was calculated in the control group of each study. 25 The prevalence rates of the C allele obtained from the individual studies were pooled together in the overall population or in various ethnic populations using the random-effects model when heterogeneity existed.…”
Section: Methodsmentioning
confidence: 99%
“…In case of heterogeneity, meta-regression analysis was performed to determine the source of heterogeneity. The year of publication, the ethnicity (Caucasian, Asian, or African-American), source of controls, genotyping method, and sample size (defined as sample size less than 500 cases, or more than 500 cases) were chosen as common variables which might be correlated to heterogeneity, 25 , 29 assessed by meta regression, and P <0.05 was considered to be statistical difference.…”
Section: Methodsmentioning
confidence: 99%
“…Study-specific RR (OR) estimates with 95%CIs for the highest versus lowest categories of dietary vitamin C intake were pooled using Z-test under fixed-effects model (Mantel-Haenszel method) if no significant heterogeneity existed 18 . Otherwise, the random-effects model (DerSimonian-Laird method) was preferred.…”
Section: Methodsmentioning
confidence: 99%
“…Although tobacco use and lipid metabolism disorder are the classical risk factors for CAD, some studies have found that CAD shows strong familial aggregation, and a gene variant is also a key risk marker for CAD patients [ 3 , 4 ]. For example, Bai et al found that the monocyte chemoattractant protein-1 (MCP-1)-2518A>G polymorphism was associated with susceptibility to CAD, especially in Caucasians [ 5 ]. By contrast, Zhang et al found that the COX-2–765G>C (rs20417) polymorphism was protective against CAD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%